Effective Approach of Activated Jordanian Bentonite by Sodium Ions for Total Phenolic Compounds Removal from Olive Mill Wastewater - Khansaa Al-Essa; Ethar M. Al-Essa (Journal of Chemistry)
Olive mill wastewater (OMW) is nowadays considered a serious environmental problem, especially within the Mediterranean region. With this in mind, water shortages are also a very serious and prevalent concern in third world countries. The aim of this study is to investigate the feasibility of using Jordanian bentonite, a simple and natural clay, as a possible adsorbent to decrease the negative characteristics of raw OMW, as an approach to the development of a methodology that addresses the OMW problem without affecting freshwater resources. The purified bentonite was activated by sodium ions at room temperature. FTIR, XRD, TGA, and BET surface area measurements were performed. OMW was contacted with both purified and activated bentonite in the batch technique to figure out the optimum parameters for the adsorption process. Physiochemical parameters of OMW were measured before and after treatment. The maximum adsorption qm was found as 8.81 mg/g at 323 K for the total phenolic compounds. The Langmuir and Freundlich models were utilized to describe the equilibrium isotherms and both models fit well. The parameters of thermodynamic show that the adsorption process was feasible, spontaneous, and endothermic in nature. These promising results along with the sodium activation of bentonite significantly improve bentonite’s adsorption capacity.